Long-term survival in a patient with primary refractory AML after salvage allogeneic hematopoietic transplantation and post-transplant localized irradiation and venetoclax maintenance: a case report - Fan, Yili; Wang, Luyao; Chen, Boxiao; Zhang, Jiawei; Yang, Luyu; Qiu, Xi; Jiang, Huawei; Zhu, Lei; Wang, Chao; Xu, Yang (Frontiers in Oncology, 2023)
For patients with primary refractory AML, allogeneic hematopoietic cell transplantation (allo-HCT) is considered the only curative approach. However, the therapeutic efficacy of salvage transplantation in the non-remission (NR) state remains controversial. We present a patient with primary refractory AML and concomitant central nervous system (CNS) leukemia, who received salvage allo-HCT, localized radiotherapy and venetoclax maintenance. Although he experienced systemic chronic graft-versus-host disease (cGVHD), he remained disease-free for 2 years. We propose that salvage transplantation is a feasible for primary refractory AML and discuss strategies to prevent relapse after allo-HCT, including maintenance therapy and donor lymphocyte infusion (DLI). Finally, we highlight the importance of radiotherapy, which can exert immunomodulatory effects to enhance immune responses against leukemia.